Supervivencia y mortalidad de una plantacion con 17 especies de regeneración natural para la restauración de bosques en la comunidad 7 Junio, Distrito De Puinahua, Loreto. 2022 - Alvarado Reategui, Carlos Marcos (2023)
Both survival and mortality were evaluated in 17 species from a plantation with natural regeneration in Puinahua, Loreto. In obtaining the results of the first evaluation, it presents an 87.40% total average, considered a very good survival. Presenting 10 species with higher percentages and ranges. Therefore, the species ray balsa with 57.93%, presents the lowest percentage. In the second evaluation it presents an 80.16% total average, considered a very good survival. In addition, the species ubos (Spondias mombin) with 93.05%, presents the highest percentage and range of 80 to 100. In the third evaluation it presents an 71.45% total average, considered a good survival. The bolaina species (Guazuma crinita) with 88.24%, has a higher survival percentage and a range of 80% to 100%, in addition, the cetico colorado species with 25.00%, has a lower percentage. In the mortality rate in the period 2021-2022, the species with the highest percentage is the cetico colorado (Cecropia distachya) with an average of 75.00% and the bolaina species (Guazuma crinita) has the lowest percentage with 11.76%.